A rare case report of short bowel anastomosis after acute mesenteric ischaemia in Covid-19 postive patient - Ammar , Ahmed Siddique; Naqi, Syed Asghar; Ashraf, Muhammad; Saleem, Maria; Raza, Hafiz Ahmed; Umbreen Haider (Journal of the Pakistan Medical Association, 2022)
Acute mesenteric ischaemia is one of the serious abdominal surgical emergency, which has got very high morbidity and mortality. During the pandemic of COVID -19, besides respiratory complications, the virus was causing venous and arterial thromboembolism that can lead to acute mesenteric ischaemia in otherwise healthy individuals. Early diagnosis and suitable surgical procedures are the key to the better outcome of this disease. Surgical resection of gangrenous gut, leaving healthy gut is an important step of this operation. Leaving less than 200 cm of small intestine leads to short bowel syndrome which has got its own complication. This case report is on a healthy COVID -19 positive patient who presented with acute mesenteric ischaemia. After surgical resection only 1.5 feet small bowel (60 cm) was left behind and anastomosis was done with healthy transverse colon. ---Continue